Adherence to appointments for gestational diabetes testing and experiences with two-hour postprandial glucose test: a mixed-methods study in Ghana - Agbozo, Faith; Schuler, Christina; Jahn, Albrecht (BMC pregnancy and childbirth, 2022)
Failure to attend scheduled appointments is a common problem in healthcare. In obstetrics, diagnostic and treatment protocols for gestational diabetes mellitus (GDM) require client booking, test preparations, management and follow-up reviews. We identified the socio-demographic, obstetric and medical drivers influencing adherence to appointments for GDM testing and experiences of pregnant women’s regarding performing oral glucose tolerance test (OGTT).